2006
DOI: 10.1111/j.1439-0442.2006.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Outer Membrane Proteins of Pasteurella multocida (6:B) Provides Protection in Mice

Abstract: The immunoprotective efficacy of Pasteurella multocida (6:B) outer membrane proteins (OMPs) was examined in the mouse model. Bacterial OMPs were extracted using sarkosyl method and analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and immunoblotting. Prototype vaccines were prepared using OMPs with adjuvants including dioleoyl phosphatidyl choline-based liposome and Montanide ISA206 water-in oil-in water emulsion. Antibody response to the vaccine was monitored using indirect enzyme linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…However, the 125 kDa protein which is only present in iron-limited condition and 70 kDa protein which is common for both iron-limited and iron-rich condition were found to be immunodominant with hyperimmune sera that rose against P. multocida serotype B:2 in bovine calves. More or less similar observations have been reported in the western blot analysis by previous workers [ 8 , 19 , 24 26 , 31 , 37 ]. 32 kDa and 37 kDa protein have been reported to be the most immunogenic proteins of P. multocida serotype B isolates.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the 125 kDa protein which is only present in iron-limited condition and 70 kDa protein which is common for both iron-limited and iron-rich condition were found to be immunodominant with hyperimmune sera that rose against P. multocida serotype B:2 in bovine calves. More or less similar observations have been reported in the western blot analysis by previous workers [ 8 , 19 , 24 26 , 31 , 37 ]. 32 kDa and 37 kDa protein have been reported to be the most immunogenic proteins of P. multocida serotype B isolates.…”
Section: Discussionsupporting
confidence: 90%
“…32 kDa and 37 kDa protein have been reported to be the most immunogenic proteins of P. multocida serotype B isolates. Except for these proteins, some authors also reported 16, 20, 28, 44, 48, 50, 56, 86, and 90 kDa proteins to be immunogenic [ 8 , 19 , 24 26 , 31 , 37 ]. These differences in the observations could be due to the different serotypes used in the study and/or individual animal factors in eliciting the immune response to these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil-based adjuvants (emulsions) have been used in vaccine formulations since 1945 (Aucouturier et al, 2006). Montanide ISA 206 is a safe water-in-oil-in-water emulsion commonly used in vaccine studies against animal pathogens including P. multocida (Basagoudanavar et al, 2006;Dupuis et al, 2006). It has been shown that CpG ODN in combination with Montanide ISA 206 synergistically induced higher immune responses to VP1 antigen of FMDV in mice and cattle as compared to an either CpG ODN or Montanide only formulation (Ren et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that several P. multocida outer membrane proteins (OMPs) contributed to the pathogenesis and possess immunogenic and bactericidal properties (Basagoudanavar et al, 2006;Lee et al, 2007;Tan et al, 2010). OmpH is an antigenic, surface-exposed and conserved OMP porin that is detected in 100% of bovine isolates investigated and has been mooted as a potential vaccine candidate (Dabo et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%